A single‐domain small protein Med‐ORF10 regulates the production of antitumour agent medermycin in Streptomyces. Issue 5 (17th June 2021) - Cai, Xiaofeng; Li, Caiyun; Ichinose, Koji; Jiang, Yali; Liu, Ming; Wang, Huili; Gong, Caixia; Li, Le; Wan, Juan; Zhao, Yiming; Yang, Qing; Li, Aiying
Summary: Med ‐ ORF10, a single‐domain protein with unknown function encoded by a gene located in a gene cluster responsible for the biosynthesis of a novel antitumour antibiotic medermycin, shares high homology to a group of small proteins widely distributed in many aromatic polyketide antibiotic pathways. This group of proteins contain a nuclear transport factor‐2 (NTF‐2) domain and appear to undergo an evolutionary divergence in their functions. Gene knockout and interspecies complementation suggested that Med ‐ ORF10 plays a regulatory role in medermycin biosynthetic pathway. Overexpression of med‐ ORF10 in its wild‐type strain led to significant increase of medermycin production. It was also shown by qRT‐PCR and Western blot that Med‐ORF10 controls the expression of genes encoding tailoring enzymes involved in medermycin biosynthesis. Transcriptome analysis and qRT‐PCR revealed that Med‐ORF10 has pleiotropic effects on more targets. However, there is no similar conserved domain available in Med‐ORF10 compared to those of mechanistically known regulatory proteins; meanwhile, no direct interaction between Med‐ORF10 and its target promoter DNA was detected via gel shift assay. All these studies suggest that Med‐ORF10 regulates medermycin biosynthesis probably via an indirect mode. Abstract : Med‐ORF10 homologues are widely distributed and functionally divergent in Streptomyces . Med‐ORF10 plays a positive regulatory role in medermycin biosynthesis and also shows pleiotropic effects on other biosynthetic pathways in an unknown indirect mode.